A novel process for low-sulfur biodiesel production from scum waste. (August 2016) - Ma, Huan; Addy, Min M.; Anderson, Erik; Liu, Weiwei; Liu, Yuhuan; Nie, Yong; Chen, Paul; Cheng, Beijiu; Lei, Hanwu; Ruan, Roger
Highlights: A new process was developed to convert scum to low sulfur biodiesel. Solvent extraction combined with acid washing was used to clean the scum oil. Activated carbon was integrated with reflux distillation to reduce sulfur content. 70% filtered and dried scum was converted to biodiesel with sulfur content ⩽15 ppm. Biodiesel from new process showed better properties than that from other processes. Abstract: Scum is an oil-rich waste from the wastewater treatment plants with a high-sulfur level. In this work, a novel process was developed to convert scum to high quality and low sulfur content biodiesel. A combination of solvent extraction and acid washing as pretreatment was developed to lower the sulfur content in the scum feedstock and hence improve biodiesel conversion yield and quality. Glycerin esterification was then employed to convert free fatty acids to glycerides. Moreover, a new distillation process integrating the traditional reflux distillation and adsorptive desulfurization was developed to further remove sulfur from the crude biodiesel. As a result, 70% of the filtered and dried scum was converted to biodiesel with sulfur content lower than 15 ppm. The fatty acid methyl ester profiles showed that the refined biodiesel from the new process exhibited a higher quality and better properties than that from traditional process reported in previous studies.